[Hikers on Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of hikers on Eldfell. The group walk up the brown and black rock volcano high above the black, rocky plains below. The black hills and lava fields are visible in the background at the top of the photograph. A blue river surrounds the lava field along the top edge of the photograph.